(untitled) (European Journal of Marketing and Economics, 2022)
The complete relocation of the center of life to a foreign country is a plan increasingly chosen by specific people, especially for entrepreneurial reasons. The digital nomads or expat-preneurs often emphasized in this context exhibit a particular structure of fundamental personality dimensions and can also be described as unique in the perception of specific challenges in the relocation process. In the present study, which is based on both a literature-based and quantitative approach, n = 196 subjects participated in an online survey that included scales and self-constructed items on personality structure, the possible choice of specific occupational groups as support systems, the perception of specific challenges, and other relevant aspects in the context of relocation. In addition to descriptive results and a brief review of previous scientific findings, multivariate analyses of variance were able to show that the choice of support system exerts a significant influence in the form of a decrease in stress in the context of the perception of specific challenges in the (tax) legal as well as financial areas. It also became clear that the region of origin and the destination region are related to assessing tax-legal aspects and administrative aspects in the economic context. Thus, there are significant differences between the Schengen Area and the U.S. area as the region of origin and these and (South East) Asia and Latin America as the destination region.